Pendidikan Karakter Mandiri dalam Wacan Bocah Majalah Panjebar Semangat 2023 - Bha’ta Paramitha Rosadi; Latif Nur Hasan (Concept: Journal of Social Humanities and Education, 2024)
Panjebar Selamat Magazine is a Javanese language magazine that provides various kinds of reading material, the contents of which contain character education values. Character education is the main thing, it is hoped that character education can become the most important foundation for Indonesian children to have good dignity. This research aims to explain the description and analyze the values ​​of character education in the children's discourse of Panjebar Spirit magazine. This research uses a sociological theoretical approach. The method used is qualitative descriptive analysis theory. The source of data used in this research is children's stories in the Panjebar Spirit magazine. The data used in this research are excerpts from children's stories in the Panjebar Spirit magazine. The instruments used were the researchers themselves and supporting instruments, namely the Panjebar Selamat magazine, books and stationery. Techniques for collecting data using reading, note-taking and describing techniques. The method of data analysis used in this research is by collecting data, classifying data, presenting data, and concluding data. The results of this research are independent character education, there are four parts, namely: hard work, creativity, discipline, and courage.